Assembly of the giant protein projectin during myofibrillogenesis in Drosophila indirect flight muscles - Ayme-Southgate, Agnes (BioMed Central, 2004)
BACKGROUND: Projectin is a giant modular protein of Drosophila muscles and a key component of the elastic connecting filaments (C-filaments), which are involved in stretch activation in insect Indirect Flight Muscles. It is comparable in its structure to titin, which has been implicated as a scaffold during vertebrate myofibrillogenesis. METHODS: We performed immunofluorescence studies on Drosophila pupal tissue squashes and isolated myofibrils to identify the pattern of appearance and assembly for projectin and several other myofibrillar proteins, using both wild type and mutant fly stocks. RESULTS AND CONCLUSIONS: In the first step of assembly, projectin immunolocalization appears as random aggregates colocalizing with α-actinin, kettin and Z(210), as well as, F-actin. In the second step of assembly, all these proteins become localized within discrete bands, leading ultimately to the regularly spaced I-Z-I regions of myofibrils. This assembly process is not affected in myosin heavy chain mutants, indicating that the anchoring of projectin to the thick filament is not essential for the assembly of projectin into the developing myofibrils. In the actin null mutation, KM88, the early step involving the formation of the aggregates takes place despite the absence of the thin filaments. All tested Z-band proteins including projectin are present and are colocalized over the aggregates. This supports the idea that interactions of projectin with other Z-band associated proteins are sufficient for its initial assembly into the forming myofibrils. In KM88, though, mature Z-bands never form and projectin I-Z-I localization is lost at a later stage during pupal development. In contrast, treatment of adult myofibrils with calpain, which removes the Z-bands, does not lead to the release of projectin. This suggests that after the initial assembly with the Z-bands, projectin also establishes additional anchoring points along the thick and/or thin filaments. In conclusion, during pupation the initial assembly of projectin into the developing myofibril relies on early association with Z-band proteins, but in the mature myofibrils, projectin is also held in position by interactions with the thick and/or the thin filaments.